Synthesis of polyhydroxy piperidines and their analogues: a novel approach towards selective inhibitors of alpha-glucosidase - Pandey, Ganesh; Bharadwaj, Kishor Chandra; Khan, Mohammad Islam; Shashidhara, K. S.; Puranik, Vedavati G. (Organic & Biomolecular Chemistry, 2008)
Various polyhydroxy piperidine azasugars have been synthesized from precursors 18a and 18b, obtained in both enantiomeric forms from D-ribose. Out of these polyhydroxy piperidine azasugars, 22, 39 and 20 were found to be potent as well as selective inhibitors of a-glucosidase with K(i) values ranging as low as 1.07 mu M, 16.4 mu M, and 88.2 mu M, respectively. Replacement of the hydroxy methylene moiety of 19 (K(i) 33% at 1 mM) by an amino methylene moiety (32, K(i) 36.8 mu M) showed a remarkable increase in the activity (almost 30 times). Furthermore, increasing the lipophilicity of 33 by N-alkylation with a dodecyl group (36) showed a three-fold enhancement in the activity (K(i) 217 mu M to K(i) 72.3 mu M).

Synthesis of polyfunctional quinolizidine alkaloids: development towards selective glycosidase inhibitors - Pandey, Ganesh; Grahacharya, Debasish; Shashidhara, K. S.; Khan, Mohammad Islam; Puranik, Vedavati G. (Organic & Biomolecular Chemistry, 2009)
A highly divergent route to a variety of quinolizidine alkaloids is described. The enantiomeric precursors 22a and 22b utilized for the synthesis of these alkaloids were constructed stereospecifically from the PET cyclization of the corresponding acetylene tethered alpha-trimethylsilyl amine moieties 21a and 21b, respectively, both of which were synthesised from D-ribose. The polyhydroxy quinolizidine alkaloid 7 was found to be a selective inhibitor of alpha-galactosidase with Ki 83.9 mu M. The amine analogs 18, 12 and 10 are found to be selective and potent inhibitors of alpha-glucosidase with Ki 28, 120 and 140 mu M, respectively.